Synthesis Biodiesel from Palm Oil Through Interesterification Using Imobilized Lipase Enzym as Catalyst: The Effect of Amount of Biocatalyst, Mole Ratio of Reactan, Temperature to Yield - Melina Widyawati; Renita Manurung; Ricky Afrianto (Chemical Engineering Diponegoro University, 2014)
Biodiesel usually synthesized by transesterification of triglyceride and alcohol by addition of acid or base catalyst so there is could produce a waste of chemical process. Alternative process is by using biocatalyst such as enzyme to synthesize biodiesel without chemical process waste. In this research, synthesis of biodiesel from Crude Palm Oil (CPO) that through the process of degumming and methyl acetate as acyl donor has been investigated with using Lipozyme as biocatalyst. Variables in this research are amount of biocatalyst, mole ratio of reactant, and temperature, and its respond to the yield conversion of biodiesel that presented by using Response Surface Methodology (RSM). Yield raging from 15% - 68% were achived during 10 hours reaction time. The results showed that the most influential variable is amount of biocatalyst.